Comparative of Active Compound in 6 Black Glutinous Rice Species - ชูเชิด พรพาชื่น; เรียบร้อย คิม ศิริพร; อุทัยพัฒนาชีพ อัญชนีย์ (Progress in Applied Science and Technology, 2017)
This research was aimed to conduct a cross-comparative study on the presence of active compound in six kinds of Thai Black glutinous rice. The six rice samples, namely, Kumking, Kumdoisaket, Kumpayao, Kaoneawdam Homphukeaw, Kaokumpae and Kaoneadam Leumpua, were collected from different areas of Thailand. Rice samples were milled, grinded and passed through 60 mesh. After that, rice powder samples were finally extracted. The extracted rice samples were stored in brown bottle and kept in -20°C. All extracts were analyzed in total phenolic, total anthocyanin, cyanidin-3-glycoside and antioxidant activity by DPPH scavenging activity method. Moreover, all of data have active compound that were significantly different at p < 0.01 statistical significance. The result showed that Kumpayao had the highest total phenolic compound (0.31 ± 0.03 mg/g). The total anthocyanin contents of Kumpae showed highest in terms of content (48.19 ± 5.05 mg/l) while Kumdoisaket showed highest in terms of cyanidin-3-glycoside content (34.49 ± 2.80 mg/l). Lastly, the Kumking had highest antioxidant activity SC50 at 5.31 ± 1.26 mg/ml.